Internet or store? An ethnographic study of consumers' internet and store-based grocery shopping practices. (September 2016) - Elms, Jonathan; de Kervenoael, Ronan; Hallsworth, Alan
Abstract: Drawing on practice theory, this paper develops an understanding of the interrelationships between where and when consumers shop (the internet, stores, and their preferred retailers), and what they purchase (via the internet and in-store). Ethnographic case studies are presented of two consumers' internet and store-based shopping practices, and how these intersect with their everyday lives, using data generated from multiple, complementary methods over an eighteen-month period. To this end, the paper contributes to the extant internet grocery shopping literature by offering a wider understanding of internet usage, as well as to broader debates surrounding retail change and shopping practices. The managerial implications of internet shopping on the contemporary retail grocery environment are also described and discussed. Highlights: An understanding of where and when consumers shop and what they purchase is developed. Two consumers' internet and store-based shopping practices are presented. Managerial implications of internet grocery shopping are considered.